How Entrepreneurial Competence and Leadership Style Affect Business Performance - Yuningsih, Nining; Putra, Ilham Muhammad Mardi; Purnamasari, Pupung; Afandi, Dian Rachmawati (Almana : Jurnal Manajemen dan Bisnis, 2024)
This research is based on the importance of entrepreneurial skills and leadership style in influencing business performance, especially for women entrepreneurs. In the age of globalization and increasingly intense competition, women entrepreneurs must possess sufficient skills and apply efficient leadership styles in order to achieve the best business outcomes. The purpose of this study is to determine the extent to which entrepreneurial skills and leadership styles impact the business performance of women entrepreneurs. This study involved women entrepreneurs in Bekasi district with 100 respondents randomly selected as the research sample. Information was collected using a questionnaire and analyzed using the Smart PLS (Partial Least Squares) technique to test the research model and hypotheses. The analysis found that entrepreneurial ability and leadership style have a major impact on firm performance. The entrepreneurial capability has been shown to make a significant contribution to improving operational efficiency and the ability to innovate, while a flexible and inspiring leadership style is able to improve team motivation and performance. It was found that it is important for women entrepreneurs to develop appropriate competencies and leadership styles to support their business success.